pVEC hydrophobic N-terminus is critical for antibacterial activity - SARIYAR AKBULUT, BERNA (WILEY, 2018)
Cell-penetrating peptides (CPPs) are commonly defined by their shared ability to be internalized into eukaryotic cells, without inducing permanent membrane damage, and to improve cargo delivery. Many CPPs also possess antimicrobial action strong enough to selectively lyse microbes in infected mammalian cultures. pVEC, a CPP derived from cadherin, is able to translocate into mammalian cells, and it is also antimicrobial. Structure-activity relationship and sequence alignment studies have suggested that the hydrophobic N-terminus (LLIIL) of pVEC is essential for this peptide's uptake into eukaryotic cells. In this study, our aim was to examine the contribution of these residues to the antimicrobial action and the translocation mechanism of pVEC. We performed antimicrobial activity and microscopy experiments with pVEC and with del5 pVEC (N-terminal truncated variant of pVEC) and showed that pVEC loses its antimicrobial effect upon deletion of the LLIIL residues, even though both peptides induce membrane permeability. We also calculated the free energy of the transport process using steered molecular dynamic simulations and replica exchange umbrella sampling simulations to compare the difference in uptake mechanism of the 2 peptides in atomistic detail. Despite the difference in experimentally observed antimicrobial activity, the simulations on the 2 peptides showed similar characteristics and the energetic cost of translocation of pVEC was higher than that of del5 pVEC, suggesting that pVEC uptake mechanism cannot be explained by simple passive transport. Our results suggest that LLIIL residues are key contributors to pVEC antibacterial activity because of irreversible membrane disruption.
Keywords: antibacterial activity; cell-penetrating peptide; free energy calculations; pVEC; replica exchange umbrella sampling; steered molecular dynamics; uptake mechanism; CELL-PENETRATING PEPTIDES; MOLECULAR-DYNAMICS SIMULATIONS; FREE-ENERGY CALCULATIONS; HIV-1 TAT PEPTIDE; INTERNALIZATION MECHANISMS; ANTIMICROBIAL PEPTIDES; PLASMA-MEMBRANE; LIPID-BILAYERS; FORCE-FIELD; ARGININE